PERGESERAN PARADIGMA PENEGAKAN HUKUM LINGKUNGAN: DARI MEKANISTIK-REDUKSIONIS KE HOLISTIK-EKOLOGI - Muhammad Akib (Masalah-Masalah Hukum, 2014)
Basically environmental destruction caused by the strong of paradigm in modern science “mechanistic- reductionist”. The progress very influences of law positivism paradigm. Positivism paradigm reduces the nature of law, thus focusing to formal procedures which contributing to the failure of environmental law enforcement. Law enforcement in the holistic-ecology paradigm should be based on three things, i.e. first, using entire legal instruments, especially administrative law, and criminal law and private law comprehensively; second, priority to sustainable of ecology than the others; and third, to enforce of law based on the values of truth and justice